Interfacial adhesion of fibre matrix by using single fibre pullout evaluation - SIm, Xinming. (2013)
This report focuses on the interfacial shear stress properties of the matrix fibre interface. Different treatment of the matrix, primer and fibre interface were experimented to evaluate the effect of each of the experimental parameter on the overall interfacial shear strength of the fibre – matrix interface.